Why Do Temporary Workers Have Higher Disability Insurance Risks Than Permanent Workers? - Pierre Koning; Paul Muller; Roger Prudon (Tinbergen Institute, 2022)
Workers with fixed-term contracts typically have worse health than workers with permanent contracts. We show that these differences in health translate into a substantially higher (30%) risk of applying for disability insurance (DI) in the Netherlands. Using unique administrative data on health and labor market outcomes of all employees in the Netherlands, we decompose this differential into: (i) selection of workers types into fixed-term contracts; (ii) the causal impact of temporary work conditions on worker health; (iii) the impact of differential employer incentives to reintegrate ill workers; and (iv) the differential impact of labor market prospects on the decision to apply for DI benefits. We find that selection actually masks part of the DI risk premium, whereas the causal impact of temporary work conditions on worker health is limited. At the same time, the differences in employer commitment during illness and differences in labor market prospects between fixed-term and permanent workers jointly explain more than 80% of the higher DI risk.
Keywords: H53; J08; I1; 330; Disability Insurance; Temporary Work; Employer Incentives; Worker Health